Standard specification for seamless and welded carbon and alloy-steel tubes for low-temperature service. (American Society of Testing Materials, 2004)
This specification2 covers several grades of minimumwall-thickness, seamless and welded, carbon and alloy-steel tubes intended for use at low temperatures. Some product sizes may not be available under this specification because heavier wall thicknesses have an adverse affect on low-temperature impact properties.